2019
DOI: 10.1021/acssuschemeng.9b06321
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and Practical Access to Epoxides: Metal-Free Aerobic Epoxidation of Olefins Mediated by Peroxy Radical Generated In Situ

Abstract: A sustainable and practical protocol to prepare epoxides has been established by using air as the oxidant in the presence of K2CO3 in isopropylbenzene (CM) at 80–140 °C. The olefins are successfully converted into their corresponding epoxides in yields of up to 99%. CM and K2CO3 are reused in the scale-up recycling experiments. A reaction mechanism dominated by the radical pathway is proposed according to the control experiments and kinetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Subsequently, • R reacted with molecular oxygen to form superoxide • OOR (formula 3), and lastly, the superoxide • OOR reacted with CM to form CHP (formula 4). 56 Formulas 5 and 6 are the two main side reactions in the oxidation reaction of CM, generating BP (ROH) and AP (ROCH 3 ), respectively. 57 To further understand the photocatalytic oxidation reaction mechanism for the oxidation of CM using the g-C 3 N 4 -2 photocatalyst, a series of control experiments with different free-radical scavengers were conducted, and the results are shown in Figure 11a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequently, • R reacted with molecular oxygen to form superoxide • OOR (formula 3), and lastly, the superoxide • OOR reacted with CM to form CHP (formula 4). 56 Formulas 5 and 6 are the two main side reactions in the oxidation reaction of CM, generating BP (ROH) and AP (ROCH 3 ), respectively. 57 To further understand the photocatalytic oxidation reaction mechanism for the oxidation of CM using the g-C 3 N 4 -2 photocatalyst, a series of control experiments with different free-radical scavengers were conducted, and the results are shown in Figure 11a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the reaction of singlet oxygen with para-substituted phenols produces nucleophilic oxygen via the formation of a hydroperoxide prone to react with electrophilic partners. For instance, the epoxidation of electron-deficient olefins under basic conditions using different oxygen sources such as hydrogen peroxide, [8] t-butyl hydroperoxide [9] or cumene hydroperoxide [10] have been widely described in literature. [11] In addition, we [12] and other groups [13] have successfully leveraged the potential of the photooxygenation/epoxidation strategy for the preparation of epoxyquinols under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is well confirmed that peracids are in situ generated from aldehyde aerobic oxidation and sequentially react with CvC bonds, giving rise to epoxide and carboxylic acid, respectively. [10][11][12][13][14] In the past several decades, both homogeneous and heterogeneous co-oxidation catalysts based on various transition metal elements, such as Mn, Fe, Co, Ni, Cu and Ru, have been widely reported in the literature. [15][16][17][18][19][20][21][22] Yet, homogeneous catalysts are difficult to be separated and reused, while the rational design and construction of heterogeneous catalysts with high distribution and thermal stability of transition metal species at the same time is still a big challenge, which needs profound understanding at the atomic scale.…”
Section: Introductionmentioning
confidence: 99%